Determination of the prevalence and antibiotic susceptibility pattern of the members of Enterobacteriaceae family from the urine samples of UTI suspected patients from a diagnostic center in Dhaka city - Haque, Syeda Samiha (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of B.Sc in Microbiology, 2018.